Biomimetic Catalysts for the Oxygen Reduction Reaction - Tasca - Gottardo; Federico (2023)
RESULTS OBTAINED: Describe the progress of your project by reference to the original objectives and/or previously modified. The maximum length of this section is 1 page (font size 10 Arial or Verdana). The oxygen reduction reaction (ORR) and the reverse reaction, the oxygen evolution reaction (OER) is of extreme importance in energy converting systems like fuel cells, and air cathode batteries, where O2 is the electron acceptor defining the potential at the cathode. Especially metal-air batteries are becoming popular again (we might say it is a vintage technology) because of the low price of the metal used at the anode (e.g. Zn) and the recent discoveries in precious metal free catalyst which can operate the two reactions i.e. the ORR and the OER. The industrial standard catalyst for the O2 involved reactions is Pt, but this metal is scarce and dear. Finally, the difficulties at overcoming the price of the catalyst, its stability and its performance are hampering the development of important technologies necessary to exit an unsustainable carbon-based economy. Another important reaction which is useful to tackle the global warming is the carbon dioxide reduction. The aims for this last year of this Fondecyt project 1181840 were: 1) to synthetize bi-fucntional catalysts for the ORR and the OER which could be employed in metal air batteries. Those catalysts could be based on penta-coordinated Fe macrocycles where the Fe phthalocyanine is coordinated to 5 N atom, one of which is axial and electron-withdrawing. 2) to measure the synthetized catalysts in terms of metal-air batteries and in terms of H2 fuel cell test station, which was one the major equipment which was bought during the 4 years together with potenstiostat and impedance modules and equipment for the synthesis of the catalyst (e.g. furnace). 3) to synthetize and to measure catalysts based on metal macrocycles for the CO2 reduction. During 2021, as a research group, we published 9 papers, (26 from the beginning of the Fondecyt 1181840) where I am the ...